Tackling Youth Inactivity and Sedentary Behavior in an Entire Latin America City - Atalla, Marcio; Pinto, Ana Jessica; Mielke, Gregore Iven; Baciuk, Erica Passos; Benatti, Fabiana Braga; Gualano, Bruno (Frontiers in Pediatrics, 2018)
Real-world interventions are fundamental to bridge the research-practice gap in healthy lifestyle promotion. This study aimed to assess the impact of a 7-month, intensive, city-wide intervention (“Life of Health”) on tackling youth inactivity and sedentary behavior in an entire Latin-American city (Jaguariuna, Brazil). For youth, a program focused on tackling inactivity/sedentary behavior was delivered at every school (n=18). Plausibility assessments (pre-to-post design) were performed with 3,592 youth (out of 8,300 individuals at school age in the city) to test the effectiveness of the intervention. Primary outcomes were physical activity and sedentary behavior. Secondary outcome was BMI z-score. Physical activity did not change (0; 95%CI:-2.7–2.8 min/day; p=0.976), although physically inactive sub-group increased physical activity levels (11.2; 95%CI:8.8–13.6 min/day; p<0.001). Weekday television and videogame time decreased, whereas computer time increased. Participants with overweight and obesity decreased BMI z-score (-0.08; 95%CI:-0.11–-0.05; p<0.001; -0.15; 95%CI:-0.19–-0.11; p<0.001). This intervention was not able to change the proportion of physical inactivity and sedentary behavior in youth at a city level. Nonetheless, physically inactive individuals increased PA levels and participants with overweight and obesity experienced a reduction in BMI z-score, evidencing the relevance of the intervention. Education-based lifestyle programs should be supplemented with environmental changes to better tackle inactivity/sedentary behavior in the real-world.